Association of Aortic Pulse Wave Velocity with the Severity of Coronary Artery Disease in Patients with Non-ST-Segment Elevation Myocardial Infarction (Bangladesh Heart Journal, 2021)
Background: Noninvasive assessment of arterial stiffness with aortic pulse wave velocity (PWV) may serve as a useful adjunct to the cardiovascular risk stratification and risk management. The aim of this study was to evaluate the association between aortic PWV and severity of coronary artery disease (CAD) in patients with non-STsegment elevation myocardial infarction (NSTEMI). Methods: This cross sectional analytical study was conducted over 100 NSTEMI patients who were purposively selected and agreed to do coronary angiogram during index hospital admission. PWV was assessed noninvasively using the SphygmoCor® system on the day before coronary angiogram (CAG). Study subjects were divided into two groups on the basis of PWV. In group I: PWV was ≤10 m/sec and in group II: PWV was > 10 m/sec. Fifty patients in each group. Angiographic severity of CAD was assessed by vessel score, Friesinger score and Leaman score. Results: Vessel score 2 and 3 were significantly (p